Studi Kasus: Media Pembelajaran Interaktif dalam Meningkatkan Kemampuan Numerasi Siswa dengan Integrasi GeoGebra dan Website - Sripatmi, Sripatmi; Sridana, Nyoman; Arjudin, Arjudin; Junaidi, Junaidi (Mandalika Mathematics and Educations Journal, 2025)
This research is motivated by the low numeracy skills of students in Indonesia, particularly in mathematics, with only 28% achieving proficiency at Level 2, far below the OECD average. The research problem includes questions about the effectiveness of Interactive Mathematics Learning Media (GeoGebra and Website) in improving students' numeracy skills in Geometry Transformation material. The aim of the research is to evaluate the effectiveness of this learning media, and the results are expected to provide an alternative for teachers in enhancing students' numeracy skills, which is crucial in addressing the wide educational quality gap in Indonesia compared to other countries, especially in terms of students' numeracy abilities. This research is also expected to provide recommendations to support the improvement of mathematics education quality at the junior high school level. This study is a case study involving 2 teachers and 8 students. The interactive mathematics learning media, integrating GeoGebra and the website, is effective in improving students' numeracy skills in geometry transformation material. The effectiveness of the interactive mathematics learning media can be seen through sufficient activities that allow students to explore the properties of translation, rotation, reflection, congruence, and dilation. Students' understanding of these properties in geometry transformation is followed by activities in solving geometry-related problems. Finally, conclusions are drawn on techniques for solving problems related to geometry transformation material.